Pijakan Strategi Kebijakan STIT Raden Wijaya Mojokerto dalam Implementasi Pengorganisasian Pembelajaran Berbasis Riset dengan Pendekatan Al Qur’an. - Eva Yulianti (PROGRESSA: Journal of Islamic Religious Instruction, 2017)
Generally the learning approach is in accordance with Islamic principles in all respects, because learning and seeking knowledge are the most commendable activities in Islam. References from the Qur'an and the Prophet's tradition suggest that learning is mandatory for every man and woman, and must be regarded as the most important thing in life. This study aims: to describe the STIT Raden Wijaya Mojokerto policy strategy footing in the implementation of organizing research-based learning with the Al Qur'an approach. The implementation of research-based methods in the teaching of Islamic education has proven to be good both in concept and in practice. something very important to consider, especially in terms of Islamic learning abilities and habits and the level of students' mastery of learning. Performance assessment is very important as an effective evaluation tool in learning. In general this refers to self-evaluation and lessons learned, and usually it relates to the purpose of life and divine guidance. Because the climate for learning also implies voluntary learning